MiRNA-27b Regulates Angiogenesis by Targeting AMPK in Mouse Ischemic Stroke Model. (1st February 2019) - Yuan, Yimei; Zhang, Zhaoguang; Wang, ZhenGang; Liu, Jinlan
Highlights: Inhibition of MiR-27b increases AMPK signaling activity. Activation of AMPK by anti-miR-27b enhances angiogenesis in vitro and in vivo. Anti-miR-27b improved neurological outcomes after ischemic stroke. Abstract: Stroke is a leading cause of mortality and serious disability worldwide with limited treatment options. Angiogenesis has been reported to be involved in post-stroke recovery. Although the molecular mechanisms that regulate angiogenesis remain ambiguous, microRNAs have emerged as effective regulators of angiogenesis, involved in neurological function outcome. The present study aims to investigate the regulatory effects of miRNA-27b on post-stroke angiogenesis. In primary cultured brain microvascular endothelial cells (BMECs), the inhibition of miRNA-27b induced the activation of adenosine monophosphate-activated protein kinase (AMPK), which increased tube formation and migration. This action was attenuated when AMPKα2 was knocked down. Mice were subjected to middle cerebral artery occlusion (MCAo) surgery and administrated with Lentivirus miR-27b inhibitor. Enhanced angiogenesis in ischemic boundary zone (IBZ) was observed, and the neurological outcome during the entire study period was improved. The number of phosphate-AMPKα2 + cells that co-expressed endothelial cell marker CD31 was significantly increased. Taken together, the present study demonstrated that downregulated miRNA-27b promoted recovery after ischemic stroke via AMPK stimulus.